059 Impact of access to MRI on neurology inpatients in a tertiary referral hospital. (23rd August 2021) - Dunn, Alexander E; Swart, Grace; Burrell, James R
Abstract : Objectives: Magnetic resonance imaging (MRI) is critical for neurological diagnosis. A major challenge remains access to timely inpatient MRI. This study aims to investigate how delayed access to inpatient MRI may impact time to diagnosis, time to definitive treatment, length of stay, and ultimately hospital budgets in an Australian Tertiary Hospital. Methods: The present study assessed the effect of MRI wait times on time to discharge in neurology inpatients at Concord Repatriation General Hospital (Sydney, Australia), a 750-bed tertiary referral hospital with one MRI scanner, between 1 September and 30 November 2020. Data was analysed using descriptive statistics. Results: The study included 84 patients. Average MRI wait time was 2.1 days. The most common indication for MRI was exclusion of stroke not identified on CT. Overall, 26% of patients experienced a delay to discharge while waiting for MRI. The delay to discharge for these patients was 1 to 4 days, with a median of 1 day. 30% of MRIs allowed same day discharge. The MRI result changed management in 88% of patients. Conclusion: A significant proportion of patients experienced delay to discharge due to delay of inpatient MRI. The result of MRI changed treatment plans for most patients, and allowed same day discharge in almost one third of cases. Timely access to inpatient MRI is a critical and potentially modifiable variable that may reduce length of stay and expedite treatment for neurology inpatients.